1996
DOI: 10.1164/ajrccm.154.2.8756806
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between nocturnal nasal positive pressure ventilation combined with oxygen therapy and oxygen monotherapy in patients with severe COPD.

Abstract: We evaluated the benefits of O2 therapy and nocturnal nasal positive pressure ventilation (NPPV) with or without O2 in patients with severe chronic obstructive pulmonary disease (COPD). Twelve patients with severe COPD and nocturnal oxygen desaturation, who had not been receiving long-term O2 therapy and who could tolerate more than 2 wk of NPPV therapy, were enrolled in this study in a stable condition. Data on pulmonary function tests (PFTS), arterial blood gases (ABG), right and left ventricular ejection fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
0
8

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 30 publications
9
92
0
8
Order By: Relevance
“…This result should be contrasted with the finding that, in a short-term study, sleep quality after 2 weeks of NIV was worse than that with oxygen therapy [52].…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 59%
“…This result should be contrasted with the finding that, in a short-term study, sleep quality after 2 weeks of NIV was worse than that with oxygen therapy [52].…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 59%
“…While there is no widely accepted definition of low-pressure and high-pressure NIV, there has been work to suggest that degree of IPAP may relate to outcome, and there has been an increasing trend towards the use of higher pressures in more recent studies 32,33 compared with older studies. 34,35 The type of NIV most useful to COPD is not clear; neither are the optimal pressure setting and optimisation protocol. It is likely that there will be significant patient variability and individualised protocols will be required.…”
Section: Types Of Non-invasive Ventilationmentioning
confidence: 99%
“…There have been few controlled trials, those of which used small numbers of patients followed over a short period of time [17][18][19][20]. Only one study showed any benefit from the combination of NPPV and long-term oxygen therapy (LTOT) [19], with the others failing to show any advantage to using NPPV.…”
Section: Mw Elliottmentioning
confidence: 99%